HISTORICAL REVIEW OF THE STATUS OF MATHEMATICS EDUCATION IN KAZAKHSTAN BEFORE THE OCT REVOLUTION - Abylkassymova, А.Е.; Kossanov, Б.М.; Khalimbetov, Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article examines the historical development of mathematical education in Kazakhstan prior to the October Revolution of 1917. The study analyzes the characteristics of arithmetic instruction in Muslim schools, as well as the methods of teaching mathematics in Russian-Kazakh and Russian-native schools. Additionally, the pedagogical transformations of the second half of the 19th century and the role of mathematics textbooks are described. The research methods include historical-comparative analysis, systematization of pedagogical data, and examination of archival documents. The development of mathematical education in pre-revolutionary Kazakhstan was complex and multifaceted, shaped by the influence of diverse educational systems. This study provides insight into the continuity of mathematical education in Kazakhstan and identifies the factors that influenced its evolution.